A case of a pulmonary mucosa‐associated lymphoid tissue lymphoma with chromosomal aberration (49, XX, +3, +i(6)(p10), +mar) - Toshihiro Ojima; Takahiro Homma; Yoshifumi Shimada; Naoya Kitamura; Yushi Akemoto; Naoki Yoshimura (Respirology Case Reports, 2019)
We report a case of a primary pulmonary mucosa‐associated lymphoid tissue (MALT) lymphoma with chromosomal aberration (49, XX, +3, +i(6)(p10), +mar). A 59‐year‐old woman was referred to our hospital for an abnormal chest shadow detected during a routine health check‐up in 2014. Chest computed tomography revealed a 3.2‐ × 2.3‐ × 2.0‐cm tumour shadow in the right middle lobe. Transbronchial biopsy did not result in the diagnosis of the tumour. Accordingly, as the tumour could have been malignant, right middle lobectomy was performed via video‐assisted thoracic surgery. On the basis of the results of immunohistochemical staining and gene analysis, the tumour was diagnosed as a primary pulmonary MALT lymphoma with chromosomal aberration (49, XX, +3, +i(6)(p10), +mar).